International experiences of training and support of students with disabilities - Melnik Y.V; Panyukova S.V; Saitgalieva G.G; Serebryannikova O.A (Moscow State University of Psychology and Education, 2017)
The paper focuses on practices of higher inclusive education in universities of the USA, Canada and Russian Federation and provides their complex assessment. The authors explore modern effective practices of training and support of students with disabilities. The universities are evaluated according to the results of monitoring of accommodations for the disabled carried out in 2015-2016. This evaluation includes assessments made by experts during their visits to the universities as well as an overview of the development of inclusive education practices in each university and, in particular, of the measures aimed at making higher education more accessible to students with disabilities. The authors argue for the necessity of establishing new and developing already existing resource training centers in the Russian regions and discuss the issues concerning the possible use of a single base of educational, information, research and methodological resources to ensure equal access to education and effective learning for students with disabilities.